2012
DOI: 10.5296/jas.v1i1.2383
|View full text |Cite
|
Sign up to set email alerts
|

Total Factor Productivity and the Bio Economy Effects

Abstract: This paper develops a new measure of total factor productivity growth in agricultural Production which incorporates Bio Economic components effects.The new measure is called the Bio Economic-Oriented Total Factor Productivity (BTFP) index, and incorporates components of Bio Economic as liquid biofuels. BTFP measure changes in Bio Economic efficiency and can be decomposed into bio economy efficiency change (BEC), and Bio Economic technological change (BTC) components.An empirical analysis, involving 7 Central A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Improving the performance of businesses active in the field of research and biotechnology has been analyzed in a number of research articles. It has been shown that this performance indicator is closely linked to the flow of capital and productivity [73,74]. Other authors [75,76] have concluded that innovation and human capital have a positive impact on the economic performance of biotech companies.…”
Section: Estimating a Model For Computing The Performance Of Enterprimentioning
confidence: 99%
“…Improving the performance of businesses active in the field of research and biotechnology has been analyzed in a number of research articles. It has been shown that this performance indicator is closely linked to the flow of capital and productivity [73,74]. Other authors [75,76] have concluded that innovation and human capital have a positive impact on the economic performance of biotech companies.…”
Section: Estimating a Model For Computing The Performance Of Enterprimentioning
confidence: 99%